The Informal American City: Beyond Taco Trucks and Day Labor - Vinit Mukhija, Anastasia Loukaitou-Sideris (The MIT Press, 2014)
A street vendor pushes a cart with ice popsicles down the sidewalk. Periodically she rings a little bell to make her presence known. At the street corner, some day laborers solicit work by raising â€œ labor for hire â€ signs each time a motorist drives by. In the next block, passersby gaze at the array of clothing, tools, and toys displayed on the front lawn of a home. Some stop, check them out, talk with the homeowner who has organized the sale, and buy an item. In another block of single-family homes, an extended family has converted their garage into an unpermitted apartment to expand the available living space. Such informality, comprised of a multitude of activities taking place beyond the regulations of the state, is typically associated with cities of the developing world. But the neighborhood scene just described is not from Quito, Lagos, or Ahmedabad but from a city in the United States, one of the most industrialized, regulated, and economically developed regions of the planet. There is ample evidence that informality is an integral and growing part of cities in the developed world. Partly a result of globalization, deregulation, and increasing immigration flows, partly a response to economic instability and increasing unemployment and underemployment, and partly because of the inadequacy of existing regulations to address the complexity and heterogeneity of contemporary multicultural living, informal activities have proliferated in U.S. cities and are clearly reflected in their built environment. In the United States and other regions of the affluent and developed world, however, informal urbanism is understudied and often misunderstood. Planners and policymakers usually see informal activities at best as unorganized, marginal enterprises that should be ignored, and at worst as unlawful activities that should be stopped and prosecuted. Similarly, the physical settings that host such activities â€” the sidewalks and street corners, front apartments, parking lots, community gardens, and taco trucks â€” are equally understudied, though they have become an increasingly visible and relevant part of the city for a number of social groups. lawns, garage